2017
DOI: 10.1002/csr.1447
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability Performance and Assurance on Sustainability Reports: Diffusion of Accounting Practices in the Realm of Sustainable Development

Abstract: In response to investors and other stakeholders questioning the credibility of the performance information displayed in sustainability reports, companies increasingly have their sustainability reports voluntarily assured by an independent third party. However, voluntary third-party assurance on sustainability reports (SA) may vary considerably in terms of the choice of the assurance provider as well as the scope and level of assurance. In this study, the relationship between corporate sustainability performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 77 publications
(144 reference statements)
9
111
2
2
Order By: Relevance
“…This result does not offer support for 2, and it is against the greenwashing perspective explanation that is companies with poor performance employ third party and adopt selective assurance to signal that B/E is credible and reliable (Hahn & Lülfs, 2014;Odriozola & Baraibar-Diez, 2017). This result is in contrast with the prior study of (Braam & Peeters, 2018) who found that poor performers companies prefer the "low-quality assurance options" with less scrutiny, so they have more room to decouple their revealed poor performance from their actual, true performance. However, this result is in line with other numerous CSR prior studies which find a positive relation between assurance provided by the Big 4 and disclosure (Cheng, Green, & Ko, 2015;Simnett et al, 2009) to ensure that stakeholders are aware of the appropriateness of the companies' actions taken on sustainability issues (Clarkson et al, 2008).…”
Section: Correlation Matrixcontrasting
confidence: 96%
See 3 more Smart Citations
“…This result does not offer support for 2, and it is against the greenwashing perspective explanation that is companies with poor performance employ third party and adopt selective assurance to signal that B/E is credible and reliable (Hahn & Lülfs, 2014;Odriozola & Baraibar-Diez, 2017). This result is in contrast with the prior study of (Braam & Peeters, 2018) who found that poor performers companies prefer the "low-quality assurance options" with less scrutiny, so they have more room to decouple their revealed poor performance from their actual, true performance. However, this result is in line with other numerous CSR prior studies which find a positive relation between assurance provided by the Big 4 and disclosure (Cheng, Green, & Ko, 2015;Simnett et al, 2009) to ensure that stakeholders are aware of the appropriateness of the companies' actions taken on sustainability issues (Clarkson et al, 2008).…”
Section: Correlation Matrixcontrasting
confidence: 96%
“…In this context, Farooq and De Villiers () noted that the main objective of assurance is to improve sustainability reports' credibility. In addition to the above, prior literature argues that assurance provided by accounting firms is more expensive and of high quality comparing with other assurance providers (Braam & Peeters, ; Simnett et al, ). Greenwashing predicts that the companies that are more likely to be subject to public pressure and legitimacy threats due to poor sustainability performance may employ third parties to provide assurance to signal good performance (Boiral, ; Cho et al, ; Maroun, ).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Stakeholders, among whom investors are of major importance, often require companies to retain independent, external assurance of their activities (Adams & Evans, 2004;Braam & Peeters, 2018;Sethi, Martell, & Demir, 2017a), thus ensuring quality and compliance with accepted standards (Cnaan, Jones, Dickin, & Salomon, 2011;Luffarelli & Awaysheh, 2018;Martínez-Ferrero & García-Sánchez, 2017). Compliance with standards lends credibility to firms' commitment to social issues (Moratis, 2018;Shafer & Lucianetti, 2018).…”
Section: Assurance Mechanisms and Marketmentioning
confidence: 99%